2020
DOI: 10.1039/d0pp00202j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photochromic behaviour of a series of benzopyrans bearing an N-phenyl-carbazole moiety: photochromism control by the steric effect

Abstract: Five new N-phenyl-carbazole benzopyrans bearing different substitution on one of the phenyl rings at the sp3 carbon have been synthesized. Their molecular structures were investigated by X-ray and NMR analyses...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The set of sub-mechanisms worked out from Scheme 1 includes, but is not limited to, those of the primary photoprocess with a transparent photoproduct (as for photochromic diarylethenes under visible light ( Crano and Guglielmetti, 2003 ; Nakatani et al, 2016 ; Maafi and Alqarni, 2022 ; Pianowski, 2022 )), the primary photoprocess with an absorbing photoproduct (as for nifedipine, nisoldipine, and dacarbazine drugs ( Tonnesen, 2004 ; Maafi and Maafi, 2013 ; Maafi and Lee, 2015a )), the photoreversible reaction (as for stilbenoids ( Crano and Guglielmetti, 2003 ; Maafi and Al-Qarni, 2019 ), anti-cancer drugs ( Tonnesen, 2004 ; Maafi and Lee, 2015b ), and dimethylhydropropenes ( Ziani et al, 2021 )), the consecutive double photoreversible system (as for fulgides in solution or in the solid state ( Crano and Guglielmetti, 2003 ; Weerasekara et al, 2017 ; Kochman et al, 2022 ; Pianowski, 2022 ) and benzopyrans ( Frigoli et al, 2020 )), the multi-consecutive photoreaction (as for riboflavin ( Maafi and Maafi, 2016 )), and other more complex systems ( Nakatani et al, 2016 ; Scaiano, 2020 ; Malato et al, 2021 ; Pianowski, 2022 ). The mechanisms and molecular systems reviewed previously have been extensively investigated, but their photokinetic studies tended to be either performed by using the equations of thermal kinetics (e.g., first-order exponential models), using various proposed (non-analytical) equations, or employing numerical integration.…”
Section: Resultsmentioning
confidence: 99%
“…The set of sub-mechanisms worked out from Scheme 1 includes, but is not limited to, those of the primary photoprocess with a transparent photoproduct (as for photochromic diarylethenes under visible light ( Crano and Guglielmetti, 2003 ; Nakatani et al, 2016 ; Maafi and Alqarni, 2022 ; Pianowski, 2022 )), the primary photoprocess with an absorbing photoproduct (as for nifedipine, nisoldipine, and dacarbazine drugs ( Tonnesen, 2004 ; Maafi and Maafi, 2013 ; Maafi and Lee, 2015a )), the photoreversible reaction (as for stilbenoids ( Crano and Guglielmetti, 2003 ; Maafi and Al-Qarni, 2019 ), anti-cancer drugs ( Tonnesen, 2004 ; Maafi and Lee, 2015b ), and dimethylhydropropenes ( Ziani et al, 2021 )), the consecutive double photoreversible system (as for fulgides in solution or in the solid state ( Crano and Guglielmetti, 2003 ; Weerasekara et al, 2017 ; Kochman et al, 2022 ; Pianowski, 2022 ) and benzopyrans ( Frigoli et al, 2020 )), the multi-consecutive photoreaction (as for riboflavin ( Maafi and Maafi, 2016 )), and other more complex systems ( Nakatani et al, 2016 ; Scaiano, 2020 ; Malato et al, 2021 ; Pianowski, 2022 ). The mechanisms and molecular systems reviewed previously have been extensively investigated, but their photokinetic studies tended to be either performed by using the equations of thermal kinetics (e.g., first-order exponential models), using various proposed (non-analytical) equations, or employing numerical integration.…”
Section: Resultsmentioning
confidence: 99%
“…[ 30,31 ] Indeed, it is known that trans‐cis coloured isomers (TC) could upon prolonged irradiation, evolve into more stable trans–trans open isomers (TT) responsible for a persistent coloration. [ 32,33 ] These results prove that the strategy of increasing the bulkiness of the substituents attached on the indene unit is a powerful and efficient method to control the kinetics of decolouration without altering the colourability at the PSS.…”
Section: Resultsmentioning
confidence: 81%
“…Indeed, it was demonstrated that trans-cis colored isomers could upon prolonged irradiation, evolve into the more stable transoidtrans open isomers (TT) responsible for a persistent coloration. [29] 2.3. Dye-Sensitized Solar Cells…”
Section: Dft Calculationsmentioning
confidence: 99%